PENGARUH CAMPURAN BAHAN BAKAR PERTAMAX-ETANOL 20% TERHADAP EMISI MESIN BENSIN KAPASITAS 150CC - Fitriyanto, Muhammad Tegar (Nozzle : Journal Mechanical Engineering, 2024)
Ethanol is an alternative fuel that can be used as a substitute for gasoline and as a gasoline fuel mixture that can be injected directly into the combustion chamber. The procedures to be carried out in the preparation stage are as follows: 1.Preparing firstx and ethanol. 2.Checking the Gas Analyzer equipment. 3.Prepare the equipment that will be used to conduct the test. Based on the test results, average calculations and data analysis conducted on exhaust emissions of 150 cc motorcycle fueled by firstx (P100) and firstx-ethanol (P80E20), it can be concluded that at 2000 rpm engine speed there is a decrease in HC, CO2, NOx emissions with the largest decrease in HC emissions by 5%. When the engine speed is 3000 rpm emissions that have decreased are CO, HC, O2 with the largest reduction value occurs in HC emissions by 144%. At 4000 rpm engine speed CO, HC emissions decreased and the largest decrease occurred in HC emissions by 49%. In the Exhaust Gas Temperature (EGT) graph also displays the results of a decrease at all engine speeds, with the largest decrease occurring at 4000 rpm engine speed of 18.3%.For this reason, further research is needed on the use of pertamax and pertamax-ethanol fuels on 150cc gasoline engine exhaust emissions, in order to produce better exhaust emissions for the future. In testing, don't forget to check the gas analyzer and change the engine oil first so that the engine in use runs smoothly without any obstacles and the results obtained are maximum.